A multimodality vascular imaging phantom of an abdominal aortic aneurysm with a visible thrombus. Issue 6 (14th May 2013) - Allard, Louise; Soulez, Gilles; Chayer, Boris; Qin, Zhao; Roy, David; Cloutier, Guy
Abstract : Purpose: With the continuous development of new stent grafts and implantation techniques, it has now become technically feasible to treat abdominal aortic aneurysms (AAA) with challenging anatomy using endovascular repair with standard, fenestrated, or branched stent‐grafts. In vitro experimentations are very useful to improve stent‐graft design and conformability or imaging guidance for stent‐graft delivery or follow‐up. Vascular replicas also help to better understand the limitation of endovascular approaches in challenging anatomy and possibly improve surgical planning or training by practicing high risk clinical procedures in the laboratory to improve outcomes in the operating room. Most AAA phantoms available have a very basic anatomy, which is not representative of the clinical reality. This paper presents a method of fabrication of a realistic AAA phantom with a visible thrombus, as well as some mechanical properties characterizing such phantom. Methods: A realistic AAA geometry replica of a real patient anatomy taken from a multidetector computed tomography (CT) scan was manufactured. To demonstrate the multimodality imaging capability of this new phantom with a thrombus visible in magnetic resonance (MR) angiography, CT angiography (CTA), digital subtraction angiography (DSA), and ultrasound, image acquisitions with all these modalities were performed by using standard clinical protocols. Potential use of this phantom for stent deployment was also tested. A rheometer allowed defining hyperelastic and viscoelastic properties of phantom materials. Results: MR imaging measurements of SNR and CNR values on T1 and T2‐weighted sequences and MR angiography indicated reasonable agreement with published values of AAA thrombus and abdominal components in vivo . X‐ray absorption also lay within normal ranges of AAA patients and was representative of findings observed on CTA, fluoroscopy, and DSA. Ultrasound propagation speeds for developed materials were also in concordance with the literature for vascular and abdominal tissues. Conclusions: The mimicked abdominal tissues, AAA wall, and surrounding thrombus were developed to match imaging features of in vivo MR, CT, and ultrasound examinations. This phantom should be of value for image calibration, segmentation, and testing of endovascular devices for AAA endovascular repair.